AllIn: Inclusion and diversity at Dow in Asia Pacific - TAN, Hwee Hoon (Institutional Knowledge at Singapore Management University, 2021)
After US materials science company Dow decided to renew its focus on inclusion and diversity (I&D), it opted to use its Employee Resource Groups (ERGs) to enable its staff to embrace this cause and effect a cultural change across its locations worldwide. As this case focuses on Dow’s efforts in Asia Pacific, it delves specifically into how Dow’s ERGs in Greater China, Japan, Indonesia, Singapore, and Thailand have helped raised staff awareness about I&D issues in these locations. In particular, Dow staff were educated on areas such as disability, gender equality, mental health, inter-generational workforce, and the marginalised in society through the various activities organised by the ERGs. The case discussion should enable students to achieve the following learning objectives: consider how the scope of I&D, as defined and practised in Dow, can be further expanded to better suit the needs and aspirations of its staff in Asia Pacific; explore how companies like Dow can inculcate in their management a more comprehensive understanding of I&D beyond mere superficial knowledge; and examine how I&D policies and thinking originally from the West may not necessarily suit markets in Asia Pacific.